THE EFFECT OF EDUCATIONAL GAMES IN THE TEACHING ABOUT OBJECT IMAGES IN KINDERGARTED STUDENTS - Nugraheni, Nawang Mustikasari (Jurnal Penelitian Pendidikan Indonesia, 2019)
Conventional learning methods in kindergarten could be changed into modern learning methods using the help of information technology in the form of educational games so that students can be motivated to learn to recognize the objects in the game. The purpose of this study is the creation of the learning media for the students in learning to recognize the names of animals and to attract learning interest of the students in using educational games as an alternative learning medium. This study employed Research and Development design (R & D). The results of the study showed the validity of the material aspect was 89.3%and 84.3% for the media aspect. The results of children's responses according to the motivational aspect was 96.29%, the aspect of interest was 79.62%, the aspect of applicability was 90.27% and the aspect of learning advantage was 100%. Based on these results, the educational games can be applied during the learning process at Kadipiro 02 Kindergarten as teaching materials for students to increase children's interest in learning image objects. Therefore, it can be concluded that the children's learning outcome​​ has increased when using the educational games.